2018
DOI: 10.1007/s12328-018-0887-8
|View full text |Cite
|
Sign up to set email alerts
|

Gastric adenocarcinoma coexisting with a reddish semipedunculated polyp arising from Helicobacter pylori-negative normal gastric mucosa: a report of two cases

Abstract: We experienced two cases of adenocarcinoma coexisting with a hyperplastic polyp arising from Helicobacter pylori-negative normal gastric mucosa. The first case was of a 59-year-old man. Esophagogastroduodenoscopy revealed a protruding lesion measuring 4 mm in diameter on the greater curvature of the middle gastric body. The second case was of a 47-year-old man. Esophagogastroduodenoscopy showed a protruding lesion measuring 5 mm located at the greater curvature of the upper gastric body. The absence of atrophi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
16
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(18 citation statements)
references
References 20 publications
2
16
0
Order By: Relevance
“…8 A recent series reported red and semi-pedunculated gastric adenocarcinomas arising in normal mucosa. 9,10 In this patient, the color and shape of the malignancy seen with white light imaging were similar to those seen in hyperplastic polyps in H. pylori-positive mucosa. However, LCI showed endoscopic findings consistent with a malignant lesion and a background different from hyperplastic polyps.…”
supporting
confidence: 61%
See 1 more Smart Citation
“…8 A recent series reported red and semi-pedunculated gastric adenocarcinomas arising in normal mucosa. 9,10 In this patient, the color and shape of the malignancy seen with white light imaging were similar to those seen in hyperplastic polyps in H. pylori-positive mucosa. However, LCI showed endoscopic findings consistent with a malignant lesion and a background different from hyperplastic polyps.…”
supporting
confidence: 61%
“…These findings of surface pattern have been observed in several patients with similar malignant lesions and play an essential role in distin-guishing this type of cancer from a benign polyp. 9,10 We reported that early gastric cancers show orange-red, orange-white, and purple colors using LCI. 3 It is noted that red cancers imaged with white light imaging change to purple with LCI.…”
mentioning
confidence: 99%
“…Previous studies have classified Hp -uninfected GCs into 4 major histopathological types: signet ring cell carcinomas [6, 7], gastric adenocarcinoma of fundic gland (GA-FG) type [8, 9], gastric adenocarcinoma of fundic gland mucosa (GA-FGM) type [10, 11], and differentiated type GC with low-glade atypia [12]. Recently, gastric adenocarcinoma of foveolar-type (GA-FV), which is diagnosed as a differentiated type GC with low-glade atypia in Hp -uninfected GCs, has newly been categorized as a subtype of raspberry-shaped gastric cancer (RSGC) [13, 14]. We recognize GA-FV as a well-differentiated adenocarcinoma based on the Japanese Classification of Gastric Carcinoma (JCGC), although it has been described as a foveolar-type adenoma by WHO classification [14, 15].…”
Section: Introductionmentioning
confidence: 99%
“…Whether the presence of AMAG may constitute an additional risk factor for neoplastic change within GHPs remains uncertain. Some case reports have described the probable relationship between GHPs and dysplasia or carcinoma [21][22][23] . Neuroendocrine differentiation occurs in 39.6% of gastric cancer cases and occurs more frequently in poorly differentiated cancers than in well differentiated tumors 24 .…”
Section: Discussionmentioning
confidence: 99%